Devolutividade no recurso de apelação - Dardenne Neto, Edouard David Marcel (2022)
The paper starts from the determination of the concept of appeal and the role of the appeal in the review system to examine the state of the current understanding of the devolutive effect. While recognizing the importance of the historical evolution of such effect, we have investigated how the doctrine works on the matter, discussing whether the legal changes, from the Civil Procedure Code of 1939 to the Civil Procedure Code of 2015, had relevant impact as to modify the understanding and the scope of the said effect. We sought to correlate the appeal effects with the material criterion for classifying court decisions. The paper discusses how, if in any way, the devolutive effect delimits both subjectively and objectively the appeal, formulating proposals for the interpretations that emphasises the grounds for appeal and the appellant’s initiative